Analisis Produktivitas Pemanen Kelapa Sawit di PTPN III Unit Kebun Pulau Mandi - Hasibuan, Muhammad Faishal Imtiyaz; Latifa, Dara; Mangunsong, Agustinus (Jurnal Agrisep, 2025)
Oil palm harvesters are workers who are expected to have high productivity to produce good quality for the progress of the company. The productivity of oil palm harvesters is the result achieved by comparing the basis that has been given by the company with different bases depending on the work area. Factors that influence harvester productivity should be the main focus such as age, number of dependents, work experience, education and premiums. This study aims to analyze the level of productivity and factors that influence the productivity of oil palm harvesters at PTPN III Unit Kebun Pulau Mandi. The research method uses a quantitative method with data collection techniques using survey and interview methods using questionnaires. Data analysis techniques in the form of oil palm harvester productivity levels and multiple linear regression analysis, namely classical assumption tests, regression coefficients, R2 tests, F tests and t tests. The results show that the level of productivity of oil palm harvesters at PTPN III Unit Kebun Pulau Mandi is in the medium category with a harvest capacity of 1.48 tons/HK or 125 TBS. For factors that affect the productivity of oil palm harvesters at PTPN III Unit Kebun Pulau Mandi, including age, number of dependents, work experience, education and premium perception show a significant influence simultaneously. Partially, the number of dependents, education and premium perception are factors that significantly influence the productivity of oil palm harvesters at PTPN III Unit Kebun Pulau Mandi.